ANALISA ANGIN ZONAL DALAM MENENTUKAN AWAL MUSIM HUJAN DI BALI BAGIAN SELATAN - Pusparini, Nikita; T.B, Winardi; Irmawan, Decky (BULETIN FISIKA, 2015)
Zonal wind analysis has been investigated to determine the beginning of the rainy season in the southern part of Bali which is limited by 8 ° 30 'S - 8 ° 48' S and 114 ° 57 'E - 115 ° 26' E. This research used the WRPlot view, a Windows-based software with Rose Wind as the image results. By this software, the variations of monthly average surface wind can be known. The average wind conditions in the southern part of Bali is influenced by the activity of the east-west monsoon. Based on the data processing year 2003 - 2012, the beginning of the rainy season generally begins on November. From the analysis of zonal wind shown that when the zonal wind is negative, it indicates the west monsoon, so the rainfall has increased. The calculation result shows that the percentage of suitability of zonal wind analysis can be used to predict the beginning of the rainy season with a percentage of 85.00% conformity with the very good category. Keyword: zonal wind, monsoon, Wind Rose